Establishing a global network of orchid seed banks - Seaton, Phillip (Universidad de Costa Rica, 2015)
Although it would appear that very few orchid species have, as yet, become extinct in the wild, such are the threats to many orchid populations, this situa- tion appears unlikely to continue (Koopowitz, 2001). Just as significant as the loss of individual species is the erosion of genetic diversity within those species. As numbers decline the size of the gene pool reduces, and the rarer alleles begin to disappear.